A Study of Cohesive Devices in IELTS Listening Tasks - Lê Thị Anh Tuyến (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
As far as the communicative nature of speech is concerned, cohesive devices are regarded as an essential component in creating organized speech and rendering the content comprehensible to listeners; therefore, gaining a thorough understanding of cohesive devices helps listeners improve their listening skills. Based on the cohesion framework of Halliday and Hasan (1976), this study aims at finding out types of cohesive devices as well as examining syntactic and semantic features of cohesive devices commonly used in IELTS Listening Tasks. The study data, 548 samples, were taken from 92 tapescripts of Listening Section Four in 20 IELTS Books. The data was quoted, described and analysed on syntactic and semantic aspects under qualitative and quantitative approaches. Findings of the study show that there are two common types of cohesive devices in IELTS Listening Tasks, namely grammatical cohesive devices and lexical cohesive devices with the former being used more frequently than the latter. Grammatical cohesive devices consist of four kinds: reference, substitution, ellipsis and conjunction; meanwhile, lexical cohesive devices are comprised of five types: repetition, synonymy, hyponymy, antonym and collocation.